Imaging modalities for drug-related osteonecrosis of the jaw (2), Overview of the position paper on medication-related osteonecrosis of the jaw and the current status of the MRONJ in Japan - Takahiko Shibahara (Elsevier, 2019)
Summary: Since Marx reported on osteonecrosis of the jaw caused by the injectable bisphosphonates (BPs) pamidronate and zoledronate, there have been numerous reports not only in Western countries, but in Japan as well, of bisphosphonate-related osteonecrosis of the jaw (BRONJ) as a pathology similar to radiation-related osteonecrosis/osteomyelitis of the jaw, which is accompanied by exposure of the bone. Osteonecrosis of the jaw similar to that occurring with BPs is also produced with the anti-receptor activator of nuclear factor kappa-Β ligand (RANKL) antibody denosumab, a bone resorption inhibitor that has a different mode of action from BPs, and there is also a report of osteonecrosis of the jaw related to bevacizumab, an angiogenic inhibitor. Because of this, in its newest position paper (2014), the AAOMS changed the nomenclature from BRONJ to "medication-related osteonecrosis of the jaw" (MRONJ). This article presents an overview of the position paper on medication-related osteonecrosis of the jaw and the current status of the MRONJ in Japan. Keyword: Bisphosphonates, Anti-RANKL antibody, Bisphosphonate-related osteonecrosis of the jaw, Medication-related osteonecrosis of the jaw, Osteoporosis, Position paper